2002
DOI: 10.1074/jbc.m208020200
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Structure of Caenorhabditis elegans N-Glycans

Abstract: We report the fine structure of a nearly contiguous series of N-glycans from the soil nematode Caenorhabditis elegans. Five major classes are revealed including high mannose, mammalian-type complex, hybrid, fucopausimannosidic (five mannose residues or fewer substituted with fucose), and phosphocholine oligosaccharides. The high mannose, complex, and hybrid N-glycan series show a high degree of conservation with the mammalian biosynthetic pathways. The fuco-pausimannosidic glycans contain a novel terminal fuco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 55 publications
4
70
0
Order By: Relevance
“…These substrates are utilized by core ␣1,3-fucosyltransferases from plants and insects (26,44), as well as by the core ␣1,6-fucosyltransferase of C. elegans. 4 It was only when we wished to rule out that the native core ␣1,6-fucosyltransferase could utilize MM that we detected a core fucosyltransferase in wild-type C. elegans extracts capable of transferring to this structure. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These substrates are utilized by core ␣1,3-fucosyltransferases from plants and insects (26,44), as well as by the core ␣1,6-fucosyltransferase of C. elegans. 4 It was only when we wished to rule out that the native core ␣1,6-fucosyltransferase could utilize MM that we detected a core fucosyltransferase in wild-type C. elegans extracts capable of transferring to this structure. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, it has become obvious that the glycosylation of invertebrate glycoproteins is significantly different from that of mammals, but although organisms such as Caenorhabditis elegans have been studied to a great extent in terms of molecular and developmental biology, an exact understanding of their glycosylation has lagged behind. Recently, however, a number of studies have indicated that the glycoconjugates of C. elegans have a number of unusual features (1)(2)(3)(4)(5)(6). None of the studies published so far agree absolutely as to the types of N-linked oligosaccharides, but the consensus would appear to be that this organism has a range of N-glycans carrying one or many fucose residues, with or without methyl or phosphorylcholine groups, as well as the standard oligomannose structures (7).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Oligosaccharides were permethylated using the method of Ciucanu and Kerek [35] with minor modifications as described previously [36]. Sample recovery was 70% to 95% based on phenol sulfuric acid assay for neutral hexose and/or peak intensity on MALDI-TOF MS analysis using permethylated oligosaccharide standards.…”
Section: Permethylation Of Oligosaccharidesmentioning
confidence: 99%